The Combination of Insulin Therapy and Diabetic Foot Exercises in Reducing Blood Glucose Levels and Improving Peripheral Perfusion in a Patient with Type 2 Diabetes Mellitus: A Case Report - Jolanda May Shinta Dewi; Zaqqi Ubaidillah (Jurnal Ilmiah Multidisiplin, 2026)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia due to insulin resistance and impaired insulin secretion. Poor glycemic control may increase the risk of peripheral vascular disorders, neuropathy, diabetic foot ulcers, and lower-extremity complications. In addition to insulin therapy, diabetic foot exercises may support glucose utilization, improve peripheral circulation, and enhance lower-limb perfusion. This study used a case report design with a nursing care process approach involving a 62-year-old female patient diagnosed with type 2 diabetes mellitus. The intervention consisted of prescribed insulin therapy and diabetic foot exercises performed once daily for seven consecutive days. Random blood glucose levels and Ankle Brachial Index values were measured before and after the intervention to evaluate changes in glycemic control and peripheral perfusion. The findings showed a gradual reduction in random blood glucose levels from 226 mg/dL on the first day to 169 mg/dL on the seventh day. The Ankle Brachial Index also increased from 0.77 to 0.87, indicating improved peripheral perfusion. These changes suggest that combining insulin therapy with diabetic foot exercises may support glucose metabolism and enhance blood flow in the lower extremities. The combination of insulin therapy and diabetic foot exercises may be considered a complementary nursing intervention to improve glycemic control and peripheral perfusion in patients with type 2 diabetes mellitus.